Two Decades of Reflection and Critique. The Continuous Fear of Replacement—The Renaissance of Feeling and Intuition in the Age of Artificial Intelligence in Qualitative Sociology Review (2005–2025) - Marciniak, Lukasz (Qualitative Sociology Review, 2026)
On the twentieth anniversary of Qualitative Sociology Review (QSR), this article offers a critical and autoethnographic reflection on how qualitative sociology has responded to technological innovation over the past two decades. I argue that the recurring fear of replacement, first by online publishing, then by CAQDAS software, and now by Artificial Intelligence (AI), reveals a persistent disciplinary anxiety. Anxiety that qualitative sociologists are being reduced to merely instrumental analytical roles. Drawing on personal recollections as a QSR co-founder and a review of global debates, I demonstrate how these fears have shaped our collective identity. Using the example of precariat research, I highlight the impor tance of the intellectualization of qualitative research, underscoring how qualitative researchers have become replaceable by technology. While AI now threatens to take over many tasks once considered the province of our expertise, it also highlights what remains uniquely human in our field: resonance, empathy, intuition, and ontological courage. I propose a competency profile for future qualitative sociol ogists that integrates digital literacy and AI collaboration with a renewed emphasis on embodied and empathetic inquiry. My conclusion presents AI not as the end of qualitative sociology, but as a catalyst for its renewal.